ANALISIS TUGAS POLISI PAMONG PRAJA DALAM PENCEGAHAN DAN PENGENDALIAN COVID-19 - Eka Ubaya Taruna Rauf; Sahrudin Sahrudin (Program Studi Administrasi Publik, FISIP, Universitas Tulang Bawang Lampung, 2022)
Enforcement carried out by the Lampung Province civil service police enforcement officers in implementing the 2020 regional regulation Number 3 regarding the adaptation of new habits in preventing, controlling COVID-19, by coordinating with the Bandar Lampung City enforcement apparatus. From the observations made by the researchers, the task of the competent authorities in carrying out COVID-19 prevention measures in implementing the Governor's Regulation has not been maximized due to the lack of budget so that operational vehicles and equipment used are limited. Besides that, many people also ignore health protocols when they are outside. This study aims to determine the duties of the Lampung Provincial Civil Service Police and to find out the Prevention and Control of Covid 19 carried out by the Lampung Provincial Civil Service Police. The research method used is qualitative research methods, data collection techniques through observation, interviews, and documentation. The task of the Civil Service Police has not been maximized in enforcing the 'Lampung Provincial Regulation Number 3 of 2020 concerning the Adaptation of New Habits in the Prevention and Control of Covid-19'. Based on the results of the study, it is known that the cause has not been maximized due to the minimal budget so that operational vehicles and equipment used are limited and in the prevention and control of Covid-19 there are still many people who do not wear masks when outside. Â Keywords: Prevention, Control, Covid-19